Relation of the protein glycation, oxidation and nitration to the osteocalcin level in obese subjects - Razny, Urszula; Goralska, Joanna; Zdzienicka, Anna; Fedak, Danuta; Masania, Jinit; Rabbani, Naila; Thornalley, Paul; Pawlica-Gosiewska, Dorota; Gawlik, Katarzyna; Dembinska-Kiec, Aldona; Solnica, Bogdan; Malczewska-Malec, Malgorzata (Acta biochimica Polonica, 2017)
Carboxylated osteocalcin (Gla-OC) contributes to the bone formation, whereas its undercarboxylated form (Glu-OC) takes part in the energy metabolism. In vitro studies had shown that treatment of osteoblast-like cells with advanced glycation end product-modified bovine serum resulted in reduced synthesis of collagen 1 and osteocalcin. The aim of this study was to find association between Gla-OC and markers of protein glycation, oxidation and nitration, as well as pro-inflammatory and antioxidant defense markers in obese subjects. Non-obese [(body mass index (BMI)<30 kg/m; n=34)] and obese subjects (30<BMI <40 kg/m ; n=98), both sexes, aged 25 to 65 years, were included in this study. Urinary glycation, oxidation and nitration free adduct concentrations were determined by stable isotopic dilution analysis liquid chromatography and mass spectrometry, and normalized to creatinine. Obese subjects had lower Gla-OC serum levels when compared to the non-obese controls. Obese subjects had increased serum concentrations of insulin, C reactive protein, interleukin 6, leptin and insulin resistance index (HOMA IR). Urinary early glycation and advanced glycation end product (AGE) free products, Nε-fructosyl-lysine and 3-deoxyglucosone-derived hydroimidazolone, respectively, and oxidative damage marker, N-formylkynurenine free adduct, were increased in the obese compared to the non-obese subjects. Serum Gla-OC was negatively correlated with urinary methylglyoxal-derived AGE, hydroimidazolone MG-H1, and N-formylkynurenine free adducts. The Gla-OC/Glu-OC index negatively correlated with the MG-H1 free adduct, and correlated positively with the antioxidant defense marker - the glutathione peroxidase activity. Our results suggest that increased AGEs and protein oxidative damage markers in the course of obesity may contribute to decreased Gla-OC level and, consequently, future risk of decreased bone formation.